Indoor location based services market drivers and challenges - Basiri, Anahid; Moore, Terry; Hill, Chris; Bhatia, Paul (2015)
Indoor Location Based Service (LBS) applications, such as indoor navigation, have not yet found a prominent position in the market as it deals with many challenges, both technical and non-technical. They include indoor positioning, availability and usability of indoor maps and privacy concerns. If these solved or handled there would be a 10 billion euro market waiting for indoor LBS. There are some upcoming and/or potential solutions and opportunities that may help to handle these challenges. They include new positioning technologies and multi-sensor positioning systems that can be applied for indoors, crowd-source mapping, change in viewpoint regarding the users privacy, standards, regulations and policies that can preserve privacy of LBS users. This paper analyses indoor LBS current markets, the challenges and trends and estimate future growth if theses challenges are handled.